The Significant Contribution Of Islamic Relationship Marketing Practice In Malaysian Takaful Industry Towards Determining Customer Gratitude, Trust, And Commitment - Che Mohd Salleh, Marhanum (Asian Academy of Management (AAM), 2016)
Parallel to the achievement of the Takaful industry, agency system becomes the main medium utilised by the industry to educate the public and assist them about future fnancial preparation. As a mirror to an Islamic type of insurance, Takaful agents play signifcant role not only to sell the Takaful products, but also to behave according to the Islamic norms in front of their customers. Thus, this research is conducted to introduce new concept of Islamic relationship marketing (IRM) and investigates its signifcance towards customer gratitude, trust, and commitment in the industry. A total of 741 of Family Takaful customers in Klang Valley area have participated in the survey conducted in this study. Few statistical analyses were performed to confrm the proposed measures of IRM including descriptive, exploratory factor analysis (EFA), measurement model, and structural equation modelling (SEM) analysis. Through EFA and measurement model, four variables were confrmed to measure the IRM which are Islamic ethical behaviour, social, structural, and fnancial bonds. Furthermore, these measures of IRM have signifcantly aﬀected customer gratitude, trust, and commitment via SEM analysis. This study serves as a starting point to promote new approach of marketing in the Takaful industry based on the Islamic norms. It basically aims to tackle the needs of Takaful participants which should be taken care by the Takaful agents as to ensure both of these parties receive benefts in the Takaful contract.